Miscellaneous Investigations in Central Tikal : Great Temples III, IV, V, and VI. Tikal Report 23B - Loten, H. Stanley (University of Pennsylvania Press, 2017)
The Maya center of Tikal, in Guatemala, is famous for its well-preserved architecture. This book presents detailed descriptions of four of the six Great Temples that dominate Tikal's city center. Whereas Great Temples I and II were published in 1990 in Tikal Report 14, the four structures presented here are Great Temples III, IV, V, and VI. All but Great Temple V represent Late Classic construction and can be associated with known rulers. It is tempting to think of these structures as funerary monuments, but this is only a supposition. Their relationship with rulers may have been much more complex. This report is the primary record of these important buildings in Tikal's urban landscape. It provides clear, precise, and usable architectural analyses for Mayanists, archaeologists, art historians, architectural historians, urbanists, and those interested in construction techniques and in the uses of Maya buildings. Museum Monograph 146.